Guest editorial: Instrumentation and measurement in the Internet-of-Things - Jardim-Gonçalves, Ricardo (2020)
The use of sensors and actuators as a way of controlling cyber-physical systems in integrated networks of digital devices has been referred to as the Internet of Things (IoT). The term IoT became popular in the late 1990s after it came up with several technologies related to the development and automation of sensors connected to the World Wide Web. Recent developments in wireless sensor networks have driven the expansion of IoT applications in a variety of areas like in industry, home, cities and healthcare. Actually, IoT technologies offer several possibilities by providing efficient and real-time operations over the Internet. However, the integration of many standalone IoT systems over the Internet introduces many challenges that require instrumentation and measurement practice to ensure the accuracy required in the application environment. For example, the advent of Industry 4.0 intends to optimize production, which will introduce new hybrid business models and exploit smart technologies while accelerating innovation cycles. Thus, several efforts have been made in industry to seek automatic cyber-physical interconnection between the virtual and physical worlds by linking the data acquired from the shop floor to manufacturing execution systems.